STABILITAS TANAH GAMBUT MENGGUNAKAN KAPUR (CaO) DITINJAU DARI PENGUJIAN KUAT TEKAN BEBAS (UNCONFINED COMPRESSION TEST) - Diana Suita; Yusrizal Lubis (Jurnal Simetri Rekayasa, 2022)
Organic soils pose many obstacles to the construction that will be built on it and are generally caused by physical properties of organic soils which have very high water content and low carrying capacity. The physical properties of a material will greatly affect the mechanical properties of the material as well as the organic soil. The mechanical properties of organic soils are very low, for example the value of free compressive strength (UCT). One method to increase the carrying capacity of the soil is by adding or mixing with materials that have a high soil carrying capacity. Adding lime to the sample in this study is expected to increase the carrying capacity of organic soil against free compressive strength (UCT). Then the sample is given the addition of lime with an additional percentage of 2%, 4%, 6%, 8%, 10% to see the comparison of the value of compressive strength (qu), after the addition of lime. The results of free compressive strength testing showed soil behavior in a sample condition with the addition of lime up to 10% experienced an increase in qu. The more the mixture of lime in the soil sample, the greater the value of free compressive strength (qu). In the original soil the value of free compressive strength (qu) was 0.837 kg / cm2, the soil was remoulded at 0.886 kg / cm2, and the free compressive strength (qu) at the addition of lime 10% was 1.132 kg / cm2.